Pengaruh Model Pembelajaran PBL Terhadap Hasil Belajar Pada Materi Soup Di SMKN 1 Lamongan - Nashita Lucky Mashura; Asrul Bahar; Niken Purwidiani; Andika Kuncoro Widagdo (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to find out the effect of problem-based learning (PBL) models on students' learning soup chapter outcomes in Class XI of Culinary at SMKN 1 Lamongan. The type of research used is a quasi-experimental with a non-equivalent control group research design. The sample was two classes, including an experimental class and a control class with 53 students in Class XI of Culinary at SMKN 1 Lamongan. Data instruments were obtained by pre-test and post-test. The data analysis technique uses an independent sample t-test test with SPSS 25. The t-test independent test results for post-test showed that the value of Sig. For 0.020, which means the significance is <0.05. It can be said that there is a significant difference in the mean. Thus, it can be concluded that there is an effect of problem-based learning model on the learning results in Class XI of Culinary at SMKN 1 Lamongan.